Caged warrior - Sitomer, Alan Lawrence (Hyperion, 2014)
From age three, McCutcheon Daniels, now sixteen, has been trained in Mixed Martial Arts and must keep winning to feed his five-year-old sister and father, but chance presents an opportunity to get out of the Detroit slums using his brain instead of his fighting skills.